A two-way interaction between methotrexate and the gut microbiota of male Sprague Dawley rats - Letertre,MPM; Munjoma,NC; Wolfer,K; Pechlivanis,A; McDonald,J; Hardwick,RN; Cherrington,NJ; Coen,M; Nicholson,J; Hoyles,L; Swann,J; Wilson,I (Journal of Proteome Research, 2020)
Methotrexate (MTX) is a chemotherapeutic agent that cancause a range of toxic side effects including gastrointestinal damage,hepatotoxicity, myelosuppression, and nephrotoxicity and has potentiallycomplex interactions with the gut microbiome. Following untargeted UPLCqtof-MS analysis of urine and fecal samples from male Sprague−Dawley ratsadministered at either 0, 10, 40, or 100 mg/kg of MTX, dose-dependentchanges in the endogenous metabolite profiles were detected. Semiquantitativetargeted UPLC-MS detected MTX excreted in urine as well as MTX and twometabolites, 2,4-diamino-N-10-methylpteroic acid (DAMPA) and 7-hydroxyMTX, in the feces. DAMPA is produced by the bacterial enzymecarboxypeptidase glutamate 2 (CPDG2) in the gut. Microbiota profiling(16S rRNA gene amplicon sequencing) of fecal samples showed an increase inthe relative abundance of Firmicutes over the Bacteroidetes at low doses ofMTX but the reverse at high doses. Firmicutes relative abundance was positively correlated with DAMPA excretion in feces at 48 h,which were both lower at 100 mg/kg compared to that seen at 40 mg/kg. Overall, chronic exposure to MTX appears to inducecommunity and functionality changes in the intestinal microbiota, inducing downstream perturbations in CPDG2 activity, and thusmay delay MTX detoxication to DAMPA. This reduction in metabolic clearance might be associated with increased gastrointestinaltoxicity.